Whole blood viscosity determination in diabetes management: perspective in practice - Nwose, Ezekiel Uba (Medknow Publications & Media Pvt Ltd, 2009)
BACKGROUND: Antiplatelet and antioxidant nutritional therapies (ANT) are commonly used in diabetes management. Guidelines recommend identifying deficiencies of antioxidant vitamins and condition of no contraindication for nutritional and antiplatelet respectively. AIM: To determine whether the guidelines recommendations for diabetes patients to be assessed for (1) antioxidant vitamins’ deficiencies and/or (2) whole blood viscosity (WBV) as indication of no antiplatelet contraindication. MATERIALS AND METHOD: Laboratory records were audited. 10,342 de-identified glycaemic index (HbA1(c)) requests received in 2008 were sorted into three groups based on level of control. (1) Poor (n = 1962, HbA1(c) ≥ 8.1); (2) Good (n = 5616, HbA1(c) = 6.0 – 8.0) and (3) Excellent (n = 2764, HbA1(c) ≤ 5.9). All 57 cases with haematocrit and total protein results in the poor (n=30) and excellent (n=27) groups were selected for calculation and comparison of WBV levels. RESULTS: None of the two guidelines’ recommendations are being followed as no case was requested for any antioxidant vitamin or WBV. Assessments of the latter show that WBV is statistically significantly lower (p < 0.05) in the group with excellent glycaemic control compared to the group with poor glycaemic control. CONCLUSION: Aspirin is one of the therapies in diabetes management. Its effect is modulated by WBV. ANT is alternative to aspirin and influences WBV. For patients that have full blood count and plasma protein results, WBV can be extrapolated at no extra cost to the health system. There is a need to raise awareness for the recommended guidelines for laboratory monitoring to be followed.